Photodriven Charge Accumulation and Carrier Dynamics in a Water‐Soluble Carbon Nitride Photocatalyst. Issue 7 (25th February 2021) - Li, Chunyu; Hofmeister, Elisabeth; Krivtsov, Igor; Mitoraj, Dariusz; Adler, Christiane; Beranek, Radim; Dietzek, Benjamin
Abstract: Charge accumulation in photoactive molecules and materials holds great promise in solar energy conversion as it allows for decoupling solar‐driven charging from (dark) redox reactions. In this contribution, light‐driven charge accumulation was investigated for a recently reported novel water‐soluble carbon nitride [K, Na‐poly(heptazine imide); K, Na‐PHI] photocatalyst, which exhibits excellent activity and stability in highly selective photocatalytic oxidation of alcohols and concurrent reduction of dioxygen to H2 O2 under quasi‐homogeneous conditions. An excellent charge storage ability of the K, Na‐PHI material was demonstrated, showing an optimal density of accumulated electrons (32.2 μmol of electrons per gram) in the presence of 10 vol % MeOH as a sacrificial electron donor. The long‐lived electrons accumulated under anaerobic conditions as K, Na‐PHI .− radical ions were utilized in interfacial electron transfer to O2 or methyl viologen in a subsequent dark reaction. Ultrafast time‐resolved spectroscopy was employed to reveal the kinetics of charge‐carrier recombination and methanol oxidation. Geminate recombination of electrons and holes within approximately 100 ps was followed by trap‐assisted recombination. The presence of methanol as a sacrificial electron donor accelerated the decay of the transient absorption signal when a static sample was used. This behavior was ascribed to the faster charge recombination in the presence of the radical anions generated after hole extraction. The work suggests that photodriven electron storage in the water‐soluble carbon nitride is enabled by localized trap states, and highlights the importance of the effective electron donor for creating long‐lived photo‐generated carbon nitride radicals. Abstract : Taking a (very) quick look : A water‐soluble carbon nitride reveals excellent storage capacity for photogenerated charges. The photoinduced dynamics in this high‐performance water‐soluble carbon nitride photocatalyst are investigated by ultrafast time‐resolved spectroscopy.